Malnutrition, anaemia and anisocytosis as public health problems among children ≤ 5 years living in malaria perennial transmission areas of Mount Cameroon: a cross sectional study - Rene Ning Teh; Irene Ule Ngole Sumbele; Gillian Asoba Nkeudem; Sorelle Mekachie Sandie; Sharon Odmia Sama; Samuel Metuge; Helen Kuokuo Kimbi (Tropical Medicine and Health, 2022)
Abstract Background Anaemia, anisocytosis, malnutrition (especially stunting) are common health problems in developing countries with children being the most vulnerable. These conditions have negative impacts on human performance, growth and development, and can further be complicated if comorbidity exists within a holoendemic stratum with strong and perennial malaria parasite transmission such as the Mount Cameroon area. The study aimed at determining the prevalence and severity malnutrition, anaemia and anisocytosis in children ≤ 5 years, living in the conflict hit malaria perennial transmission zone of the Mount Cameroon area. Method A cross-sectional community-based survey involving 628 children ≤ 5 years was conducted. Malaria parasitaemia was confirmed by Giemsa-stained microscopy and the density was log transformed. Haemoglobin (Hb), mean cell volume and red blood cell distribution width were estimated using an auto-haematology analyser and defined according to WHO standards. Anthropometric indices were analysed and compared with WHO growth reference standards using WHO Anthro software. Results Plasmodium infection, anaemia, microcytic anaemia, anisocytosis and stunting were prevalent in 36.0, 72.8, 30.1, 54.1 and 29.0% of the children, respectively. The ≤ 24 months children were more moderately stunted (14.7%), with higher prevalence of microcytic anaemia (38.8%) and anisocytosis (68.8%) (P < 0.002 and P < 0.001, respectively) when compared with the older children. The mean Hb level in the study population was 10.04 g/dL with children ≤ 24 months having the least mean haemoglobin level (9.69 g/dL) when compared with their older counterparts at P < 0.001. The odds of having anisocytosis were highest among children who were malnourished (OR = 4.66, P = 0.005), those infected with malaria parasites (OR = 1.85, P = 0.007), and whose parents had a primary (OR = 3.51, P = 0.002) and secondary levels of education (OR = 2.69, P = 0.017). Conclusion Malaria, anaemia, anisocytosis and undernutrition still ...